2009
DOI: 10.1080/00103620802625617
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Soil Organic Matter and Biomass and Labile Forms of Carbon as Influenced by Crop Rotations

Abstract: Recent concerns about the role of carbon (C) in climate change and the implications about soil organic matter (SOM) for sustainable use of soils have underlined the need to examine the role of SOM in cropping systems, particularly in fragile ecosystems. Accordingly, we examined the changes that occur in total SOM and in its more reactive fractions, labile and biomass C, within a long-term, cereal-based crop rotation trial. The rotations were wheat (Triticum turgidum var durum) grown after vetch (Vicia sativa),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…The SOM and POXC, which are indicators of the soil organic carbon, were the highest in winter and fall, and may have accumulated because of a low soil temperature, lack of soil disturbance that would expose the organic matter to oxidation, and lower microbial activity resulting in less consumption of soil organic products for energy. This result is confirmed by other studies that have found a significantly higher SOM and microbial biomass carbon in winter compared with summer [10,11]. Although the decomposition rate is slower during this period, the enzyme and microbial activities in early fall, and the plant carbon inputs and litter chemistry in winter may have increased the soil's carbon concentration [26][27][28].…”
Section: Sampling Season Effectssupporting
confidence: 80%
See 2 more Smart Citations
“…The SOM and POXC, which are indicators of the soil organic carbon, were the highest in winter and fall, and may have accumulated because of a low soil temperature, lack of soil disturbance that would expose the organic matter to oxidation, and lower microbial activity resulting in less consumption of soil organic products for energy. This result is confirmed by other studies that have found a significantly higher SOM and microbial biomass carbon in winter compared with summer [10,11]. Although the decomposition rate is slower during this period, the enzyme and microbial activities in early fall, and the plant carbon inputs and litter chemistry in winter may have increased the soil's carbon concentration [26][27][28].…”
Section: Sampling Season Effectssupporting
confidence: 80%
“…Previous studies have shown the variability that could exist, as soil quality indicators are sampled during the different months of the year within a given growing season [8][9][10][11]. Moebius et al [8] studied the temporal variations of many soil physical quality indicators within a season, in different tillage and crop rotation trials, and found that the indicators vary significantly with the sampling dates and in the different soil types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, cereal-legume rotations, while being biologically and economically attractive, also improve soil quality and advance agronomic sustainability in the harsh dryland conditions of the WANA region . The labile fraction decreased from 1,746 mg kg −1 in February to 1,275 mg kg −1 in August, and the MBC from 107 mg kg −1 in February to 71 mg kg −1 in August (Ryan et al 2009 ). The SOM concentration in the surface and sub-soil respectively, was 1.4 % and 1.1 % in medic ( Medicago spp.)…”
Section: Cropping Systemsmentioning
confidence: 93%
“…A long-term experiment at Tel Hadya, Syria showed that soil physical properties indicated parallel trends with increasing concentration of SOM . Ryan et al ( 2009 ) observed that the SOM concentration decreased from 1.48 % in February to 1.151 % in August after cropping. Kapur et al ( 2007 ) assessed the impact of several cereal-based rotations on soil quality in Aleppo, Syria.…”
Section: Cropping Systemsmentioning
confidence: 95%